Feeding Ecology of Three Euphausiid Species in the North Pacific Ocean Inferred From 18S V9 Metabarcoding and Stable Isotope Analysis - Zhou, Fanyu; Hirai, Junya; Hamasaki, Koji; Horii, Sachiko; Tsuda, Atsushi (Frontiers in Marine Science, 2021)
Euphausiids are abundant micronekton and important links between higher and lower trophic levels in marine ecosystems; however, their detailed diets cannot be fully understood by conventional microscopy, especially in subtropical areas. Here, we report the euphausiid community structure in the California Current (CC) area and the eastern/western North Pacific subtropical gyre (ESG and WSG) and detail the feeding ecology of the dominant species (Euphausia pacifica, E. brevis, and E. hemigibba) in each region using a combined approach of gut content analysis via 18S V9 metabarcoding and stable carbon and nitrogen isotope analysis. A pronounced omnivorous feeding of all studied euphausiid species was supported by both methods: phytoplanktonic taxonomic groups (Dinophyta, Stramenopiles, and Archaeplastida), Copepoda, and Hydrozoa were detected in the gut contents; all the three euphausiid species displayed an intermediate trophic position between the net plankton (0.2–1.0 mm) and the myctophid fish (15.2–85.5 mm). However, Hydrozoa found in euphausiid gut contents likely derived from a potential cod-end feeding, based on isotope analysis. E. pacifica in the CC province ingested more autotrophic prey, including pelagophyte and green algae, due to a greater abundance of Stramenopiles and Archaeplastida in shallow layers of CC water. On the other hand, non-autotrophic prey such as mixotrophic Kareniaceae dinoflagellates, Pontellidae and Clausocalanidae copepods, and Sphaerozoidae rhizarian contributed more to the diets of E. brevis and E. hemigibba because of a lower chlorophyll a concentration or potentially a scarcity of autotrophic prey availability in ESG and WSG. The feeding patterns of dominant euphausiid species conducting filter feeding were thus largely determined by phytoplankton prey availability in the environments. Dietary difference across three species was also indicated by stable isotope analysis, with a lower mean trophic level of E. pacifica (2.32) than E. brevis (2.48) and E. hemigibba (2.57). These results verify direct trophic interactions between euphausiids and primary production and suggest that the omnivorous feeding habit is a favorable character for dominant Euphausia species.